Деякі співвідношення узагальненої теорії нетонких пластин з початковими напруженнями - Кондратенко, О.А.; Хома, І.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
A system of differential equations of equilibrium of non-thin transversely isotropic plates with a similar field of initial strains is built. The general solution of the present system is found, and, on its base, the problem of a strained state of the plate weakened by a round cylindrical cavity has been considered.